Pementasan Nyanyian Orovera Manukeka Sebagai Bentuk Pelestarian Budaya Lokal - Sawe, Maria Susanti; Maria Dalupe Wea; Patrisus A. Bhia; Ferdinandus Bate Dopo; Kanzul Fikri; Hermania Bupu (Pendidikan Matematika, FKIP Universitas Mataram, 2025)
Abstract This community service aims to explain how the orovera manueka song is revived through performances to students. Therefore, support for mentoring and implementing the preservation of the ancestral heritage of the Nataia tribe, especially the orovera manukeka song, is a concern for teachers, the community, academics (universities) and the local government so that they can convey feelings, stories, or deep experiences about traditional songs. This community service is located in Aeramo Village, Aesesa District, Nagekeo Regency. The techniques used are in three stages, namely observation, interviews and documentation. The instruments that will be used are in the form of interview guidelines and cameras for documentation. The subjects in this community service are traditional functionaries, educational institutions and community leaders who are considered to have knowledge about the objects in this community service aims to explain how the orovera manueka song is revived through performances to students. Therefore, support for mentoring and implementation of the preservation of ancestral heritage of the Nataia tribe, especially the Orovera Manukeka song, is a concern for teachers, the community, academics (universities) and the local government so that they can convey feelings, stories, or deep experiences about traditional songs. This service is located in Aeramo Village, Aesesa District, Nagekeo Regency. The techniques used are in three stages, namely observation, interviews and documentation. The instruments that will be used are in the form of interview guidelines and cameras for documentation. The subjects in this service are traditional functionaries, educational institutions and community leaders who are considered to have knowledge about the objects in the performance.